Regenerative Strategies for the Treatment of Knee Joint Disabilities - Oliveira, Joaquim Miguel; Reis, Rui Luís.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book presents regenerative strategies for the treatment of knee joint disabilities. The book is composed of four main sections totaling 19 chapters which review the current knowledge on the clinical management and preclinical regenerative strategies. It examines the role of different natural-based biomaterials as scaffolds and implants for addressing different tissue lesions in the knee joint. Section one provides an updated and comprehensive discussion on articular cartilage tissue regeneration. Section two focuses on the important contributions for bone and osteochondral tissue engineering. Section three overview the recent advances on meniscus repair/regeneration strategies. Finally, section four further discusses the current strategies for treatment of ligament lesions. Each chapter is prepared by world know expert on their fields, so we do firmly believe that the proposed book will be a reference in the area of biomaterials for regenerative medicine.
Keywords: Mechanical Engineering; Biomedical Engineering and Bioengineering; Biomaterials, Solid Mechanics; Regenerative Medicine/Tissue Engineering